Preparation And Properties Of Cinnamon Essential Oil Loaded Antibacterial Nanocellulose/chitosan Aerogels For Biomedical Applications - Yahya, Esam Bashir Abdulsalam (2022)
Aerogel is a novel functional material consists of fibers scaffold and air, without water or any other solvent. Pure nanocellulose aerogel has numerous unique characteristics but it normally combined with inorganic materials to overcome its undesired drawbacks such as the high water absorption and poor mechanical properties, which favour the microbial colonization in its surfaces. The aim of this study was to isolate and characterize cellulose nano fibers (CNFs) from kenaf bast fibers using supercritical carbon dioxide (Sc.CO2) and investigate its role of Sc.CO2 in enhancing the properties of CNFs. The study also aim to fabricate and characterize antibacterial CNFs/chitosan aerogels, cross-linking the isolated CNFs with chitosan and loading the aerogel with cinnamon essential oil as the main antibacterial agent. The aerogel was fabricated using a green approach; consist of high-pressure homogenization and freeze-drying techniques. The results of CNFs isolation confirm the ability of Sc.CO2 to enhance the properties of isolated CNFs compared with non-Sc.CO2 obtained CNFs, in term of particle size, thermal properties and zeta potential value. The Sc.CO2 obtained CNFs had an average fibre length, and diameter of 53.72 and 7.14 nm, respectively, while non-Sc.CO2 obtained CNFs had longer fibre length and diameter (302.87 and 97.93 nm). Higher thermal stability and lower negativity value was also recorded for Sc.CO2 obtained CNFs. Extraction of cinnamon essential oil was conducted using Sc.CO2, which was found to be of low yield but high purity.